Teaching to the test: The effects of coaching on English-proficiency scores for university entry. Issue 1 (16th February 2021) - Trenkic, Danijela; Hu, Ruolin
Despite arriving with the required language qualifications, many international students struggle with the linguistic demands of a university degree. Using the International English Language Testing System (IELTS) as an example, this study explored how short but intensive preparation programmes may affect high-stakes English-proficiency test scores with which students apply for university places. The participants were 89 Chinese speakers of English as a foreign language in Shanghai. They were tested twice, four weeks apart, on IELTS and three other measures of English ability: The Oxford Online Placement Test, a vocabulary test, and the speed and accuracy of sentence comprehension. Between the two testing points, 45 participants underwent test-specific training consisting of previous IELTS papers, offered by a large test-preparation establishment with a network of over 1, 000 training centres. The remaining 44 participants did not engage in any test preparation at the time. Teaching to the test led to a half a band rise in IELTS scores above the gain from test repetition alone, suggesting that the training was effective. Importantly, the IELTS gain did not generalise to the other measures of English ability; the groups performed similarly on all other language tests at both times. This suggests that test-specific, curriculum-narrowing courses could be inflating the scores with which international students apply for university places, with important consequences for test-developers, universities and students.